2017
DOI: 10.1101/237529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Osterixfunctions downstream of anti-Müllerian hormone signaling to regulate Müllerian duct regression

Abstract: In mammals, the developing reproductive tract primordium of male and female fetuses consists of the Wolffian duct and the Müllerian duct (MD), two epithelial tube pairs surrounded by mesenchyme. During male development, mesenchyme-epithelia interactions mediate MD regression to prevent its development into a uterus, oviduct and upper vagina. It is well established that transforming growth factor-beta family member anti-Müllerian hormone (AMH) secreted from the fetal testis and its type 1 and 2 receptors expres… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…AMH is activated by proteolytic cleavage of proprotein, and binds specific AMH type 2 receptor [4], followed by the recruitment of SMAD signal transducer proteins [5], leading to their nuclear translocation where they regulate target gene expression [1,4,5]. Along with its role as determinant of the male sexual differentiation, changes in AMH levels, together with follicle-stimulating hormone (FSH) and luteinizing hormone (LH), reflect aging in females [6]. This age-dependent decline in fertility typically begins at the third decade of female's life and deteriorates markedly after age 35 years old.…”
Section: Introductionmentioning
confidence: 99%
“…AMH is activated by proteolytic cleavage of proprotein, and binds specific AMH type 2 receptor [4], followed by the recruitment of SMAD signal transducer proteins [5], leading to their nuclear translocation where they regulate target gene expression [1,4,5]. Along with its role as determinant of the male sexual differentiation, changes in AMH levels, together with follicle-stimulating hormone (FSH) and luteinizing hormone (LH), reflect aging in females [6]. This age-dependent decline in fertility typically begins at the third decade of female's life and deteriorates markedly after age 35 years old.…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by the multifactorial variability of the endometrial thickness (22). FSH and LH were biochemical markers reflecting aging in women, and they deteriorated significantly after the age of 35 due to the decrease in ovarian reserve (23). The Buyalos and Danesmand studies showed that the E2 level in infertile patients entered the abnormal range within two years of observation (22).…”
Section: Discussionmentioning
confidence: 99%
“…AMHR2 recruits 1 of 2 non-specific type I receptors, either BMPR1A or ACVR1, thus inducing the phosphorylation of intracellular proteins SMAD1, SMAD5, and SMAD8 (also called SMAD9) and their translocation to the nucleus, where they regulate target gene expression [Josso, 2019;Moses and Behringer, 2019]. Osterix (OSX) is induced by AMH and involved in müllerian duct regression [Mullen et al, 2018]. β-catenin is required for AMH action [Kobayashi et al, 2011].…”
Section: Amh Action On Müllerian Ductsmentioning
confidence: 99%